(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2019)
The herbal plant status in Pulau Tioman is unknown, and may be reduced due to extensive recreational activities in Kg. Tekek Waterfalls. The main objective of this preliminary survey is to assess the varieties of herbal plants that are found at Pulau Tioman, Pahang. Herbal plant survey was carried out in a transect of 5-meter width on both side of the 1 km main track connecting Kampung Tekek Jetty to Kampung Tekek Waterfalls. A total of seven species namely, Dracaena umbratica, Flagellaria indica, Selaginella willdenowii, Ixora javanica, Lygodium microphyllum, Melastoma malabathricum and Cassia alata which belong to seven (7) families namely Asparagaceae, Flagellariaceae, Selaginellaceae, Rubiaceae, Lygodiaceae, Melastomataceae and Leguminosae were collected, identified and reported. The list of plants recorded could be included in a datasheet for the study of plants with medicinal value and the distribution data could be used to update the IUCN and CABI database.